Proximate composition, phytochemical analysis and toxicity assessment of extracts of caulerpa lentillifera using autoclave- and microwave-assisted extractions - Saranya Peerakietkhajorn,; Wirawan Worakit,; Churairat Moukamnerd,; Chittipong Tipbunjong, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Caulerpa lentillifera is a marine alga widely cultured and consumed in Asia and Oceania. Emerging green techniques are currently popular for phytochemical extraction. Therefore, this study aimed to investigate the proximate compositions, phytochemicals, and antioxidant properties of the C. lentillifera extracts using autoclave-assisted and microwaveassisted extraction methods (A-CLE and M-CLE, respectively). The toxicity of extracts was tested against human normal colon cells and freshwater crustacean Daphnia magna. We found that crude lipid, ash and moisture contents in A-CLE were lower than those in M-CLE, while crude protein and crude carbohydrate were higher in A-CLE. Total flavonoid content in A-CLE (1.474 ± 0.046 mg QE g-1 extract) was higher than that in M-CLE (1.179 ± 0.054 mg QE g-1 extract). There was no difference in total phenolic contents, triterpenoid contents and antioxidant activities between the extracts. The IC50 of A-CLE (12,260 ± 197 µg mL-1) was higher than that of M-CLE (10,950 ± 169 µg mL-1). In the acute toxicity test, the LC50 of A-CLE against D. magna (7.50 ± 0.28 g L-1) was lower than LC50 of M-CLE (8.76 ± 0.26 g L-1). This study suggest that autoclave-assisted and microwave-assisted extractions are effective green methods of extracting C. lentillifera. This study will be useful for further studies of C. lentillifera extracts to improve human and animal health.